Impact of TNF-α Gene Polymorphisms on Pancreatic and Non-Small Cell Lung Cancer-Induced Cachexia in Adult Egyptian Patients: A Focus on Pathogenic Trajectories - Rana Yehia (Frontiers Media S.A., 2021)
BackgroundCachexia is a frequent syndrome in pancreatic and non-small cell lung (NSCL) cancer patients. The storm of cancer-induced inflammatory cytokines, in particular TNF-α, is a crucial pathogenic mechanism. Among the molecular alterations accused of cancer-induced cachexia, TNF-α 308 G/A (rs1800629) and −1031T/C (rs1799964) are single-nucleotide polymorphisms (SNPs) within the gene encoding this pro-inflammatory cytokine. Recent studies have demonstrated the crucial role of non-coding microRNAs (miRNAs) in pathogenesis of different diseases including cachexia. Moreover, the mechanistic cytokine signaling pathway of miR-155, as a TNF-α regulator, supports the involvement of SOCS1, TAB2, and Foxp3, which are direct targets of TNF-α gene.AimA case–control study (NCT04131478) was conducted primarily to determine the incidence of TNF-α 308 G/A (rs1800629) and −1031T/C (rs1799964) gene polymorphisms in adult Egyptian patients with local/advanced or metastatic pancreatic or NSCL cancer and investigate both as cachexia risk factors. The association of gene polymorphism with cachexia severity and the expression of miR-155 in cachectic patients were analyzed. A mechanistic investigation of the cytokine signaling pathway, involving SOCS1, TAB2, and Foxp3, was also performed.ResultsIn both pancreatic and NSCL cancer cohorts, the mutant TNF-α variant of 308 G/A was positively associated with cachexia; on the contrary, that of 1031T/C was negatively associated with cachexia in the NSCL cancer patients. MiR-155 was higher in cachexia and in alignment with its severity in the cachectic group as compared with the non-cachectic group in both the pancreatic and NSCL cancer patients. Though TAB2 did not change to any significant extent in cachectic patients, the levels of SOCS1 and Foxp3 were significantly lower in the cachectic group as compared with the non-cachectic group.ConclusionCarriers of the A allele 308 G/A gene and high miR-155 are at greater risk of cachexia in both the pancreatic and NSCL cancer patients; however, the mutant variant of 1031T/C gene is protective against cachexia in the NSCL cancer patients. Finally, high levels of miR-155 in the cachectic group lead to negative feedback inhibition of both SOCS1 and Foxp3 in both the pancreatic and NSCL cancer patients.